The risk of psychiatric disorders among Finnish ART and spontaneously conceived children: Finnish population-based register study - Rissanen E; Gissler M; Lehti V; Tiitinen A (SPRINGER, 2022)
Evidence regarding the psychiatric morbidity of children born after Assisted Reproductive Techniques (ART) is inconsistent and limited. While normal mental well-being for ART children is usually reported, concerns are still being raised. Previous studies examine only some psychiatric disorders, but not all of them, ignore the impact of multiplicity, and limit the follow-up time to childhood. We examined all psychiatric diagnoses for singletons until their young adulthood. The aim was to study whether the risk of psychiatric disorders differs between ART and spontaneously conceived (SC) singletons until young adulthood. This retrospective Finnish population-based register study includes all ART and SC live-born children born in Finland during 1990-2013 and their hospital care in 1990-2014 (n = 1,425,975 of which 1,385,956, 97.2% were singletons). After excluding multiples, the final population included 17,610 ART and 1,368,346 SC singletons in 1990-2013 from the Finnish Medical Birth Registry. These data were linked to the Finnish Hospital Discharge Registry with the child's and mother's encrypted IDs. ART singletons had fewer psychiatric diagnoses (ART 10.2%, n = 1796, SC 12.0%, n = 164,408), but they received their diagnoses earlier (mean 8.3 years old, SD 5.0) than SC singletons (mean 10.5 years old, SD 5.7). After adjusting for confounding factors, ART singletons had an increased likelihood of getting a psychiatric diagnosis until young adulthood and the results were similar for boys (adjusted hazard ratios [aHR] = 1.16, 95% confidence interval (CI) 1.10-1.24) and girls (aHR = 1.25, 95% CI 1.16-1.35). We conclude that ART children receive their psychiatric diagnoses earlier than SC children, in particular during childhood and early adolescence. After adjusting for confounding factors ART children a slightly increased likelihood of any psychiatric diagnosis compared to SC controls.